Aldo-Keto Reductases 1B in Adrenal Cortex Physiology - Pastel, Emilie; Pointud, Jean-Christophe; Martinez, Antoine; Lefrançois-Martinez, A. Marie (Frontiers in Endocrinology, 2016)
Aldose reductase proteins are cytosolic monomeric enzymes, belonging to the aldo-keto reductase (AKR) superfamily. They perform oxidoreduction of carbonyl groups from a wide variety of substrates such as aliphatic and aromatic aldehydes or ketones. The Aldose reductase subgroup (AKR1B) is one of the most characterized because of its involvement in human diseases such as diabetic complications resulting from the ability of its human archetype AKR1B1 to reduce glucose into sorbitol. However the issue of AKR1B function in non pathologic condition remains poorly resolved. Adrenal steroidogenesis is strongly associated with high production of endogenous harmful lipid aldehyde by-products including isocaproaldehyde (4-methylpentanal) derived from cholesterol side chain cleavage (the first step of steroid synthesis) and 4-hydroxynonenal (4- HNE) that can both be reduced by AKR1B proteins. More recently, some AKR1B isoforms have been shown to be endowed with prostaglandin F synthase activity, suggesting that in addition to possible scavenger function, they could instigate paracrine signals. Interestingly, previous studies have established that the adrenal gland is one of the major site for human and murine AKR1B expression suggesting that their detoxifying/signaling activity could be specifically required for the correct handling of adrenal function. Moreover chronic effects of ACTH result in a coordinated regulation of genes encoding the steroidogenic enzymes and some AKR1B isoforms. This review presents the molecular mechanisms accounting for the adrenal specific expression of some AKR1B genes. Using data from recent mouse genetic models, we will try to connect their enzymatic properties and regulation with adrenal functions.